Realism in the Post-War American Novel: Realistic portrayal of conflicts in post-war American society (Journal of Advances and Scholarly Researches in Allied Education, 2015)
The progressive drain of the country’s spiritual potential the conflict between viewpoints of different generations, the intensification of interracial and social conflicts whose bitterness could not be concealed by the deceptive rogues of this affluent society- these were the problems that the literature of critical realism dealt with in those years when American intervention in Vietnam served as a catalyst, speeding up and dramatizing many processes in the country’s internal life.